2021
DOI: 10.3389/fpsyt.2020.613368
|View full text |Cite
|
Sign up to set email alerts
|

Media Exposure to COVID-19 Predicted Acute Stress: A Moderated Mediation Model of Intolerance of Uncertainty and Perceived Social Support

Abstract: Background: Previous studies have found that disaster-related media exposure could predict acute stress responses. However, few studies have investigated the relationship between media exposure to COVID-19 and acute stress, and less is known about the mechanisms that translate media exposure to COVID-19 into acute stress. The current study explored the impact of media exposure to COVID-19 on acute stress, and examined the mediating role of intolerance of uncertainty (IU) and the moderating role of perceived so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 100 publications
(97 reference statements)
3
32
0
Order By: Relevance
“…Besides, the mediation effect suggested that social media exposure contributed to the elevated depressive symptom through psychological distress. Media exposure to COVID-19 has been found to be positively related to acute stress ( 69 ). There is considerable evidence that greater social media exposure is a risk factor contributing to depression and psychological distress in adolescents ( 70 ); further investigations are needed to clarify the potential moderators between the relationship of social media exposure and depressive severity related to COVID-19 in people of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the mediation effect suggested that social media exposure contributed to the elevated depressive symptom through psychological distress. Media exposure to COVID-19 has been found to be positively related to acute stress ( 69 ). There is considerable evidence that greater social media exposure is a risk factor contributing to depression and psychological distress in adolescents ( 70 ); further investigations are needed to clarify the potential moderators between the relationship of social media exposure and depressive severity related to COVID-19 in people of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…One such lengthy negative event is lockdowns, or large-scale movement restrictions (World Health Organization B, 2020 ). Recent studies are showing a post-lockdown acceleration in urgent and emergency mental health referrals, indicating potential long-term negative impact of lockdown on mental health (Chen et al, 2020 ). Although these findings are correlational and not causational (i.e., acceleration in mental health referrals could also be due to other causes, such as availability of services at different points of time, client fears about attending care, difficulty traveling to appointments, etc.…”
Section: Lessons From the Covid-19 Pandemicmentioning
confidence: 99%
“…This study provides a preliminary exploration of potential key antecedents of mental resilience of employees and risk factors for the occurrence of mental disorders under prolonged stress exposure. While most studies on risk communication are focused on the influence of media on employees response formation (Chong and Choy, 2018 ; Garfin et al, 2020 ; He et al, 2020 ; Manzoor and Safdar, 2020 ; Tsoy et al, 2021 ), we have undertaken to investigate how threat perception and perceived efficacy under the ongoing exposure to job uncertainty can precipitate mood disorders. There is lack of support in the literature that would explain how exposure to hazard-related information influences the formation of adaptive or maladaptive coping strategies of employees aimed at psychological well-being retention.…”
Section: Introductionmentioning
confidence: 99%